The unfinished task of the Evangelical Lutheran mission during the 21st century in the Northern Diocese, focusing much on the comprehensive mission of the church - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Dissertation (MA(Theology))--University of Pretoria, 2010.